Enabling competence in prescribing medicines across multiple healthcare disciplines through systematic assessment practices : final report. - Nissen, Lisa; Cardiff, Lynda (Australia, Dept of Education and Training, 2017)
This is the final report from a project that was focused on the development of student prescribing competence in multiple health disciplines. Prescribing is a complex task, requiring specific knowledge and skills, combined with effective, context-specific clinical reasoning. For both established and emerging professions with prescribing rights, there is a clear need to ensure graduates have well defined prescribing skills, to enable competent prescribing. Essential to this outcome is the application of comprehensive, evidence-based assessment methods that effectively assess these skills. This project investigated existing strategies employed to assess prescribing competency and developed and evaluated a consensus driven, evidence-based toolkit to guide assessment processes.